Principles of teaching academic writing as a basis for course - Rybalkina, E. A. (Язык и культура : сборник статей XXXIII Международной научной конференции (16-17 ноября 2023 г.))
This article is devoted to the principles of teaching academic writing. The article considers the text organization features. Attention is also paid to the peculiarities of teaching academic writing to university students.